2018
DOI: 10.1108/jpif-11-2017-0073
|View full text |Cite
|
Sign up to set email alerts
|

Identifying the risk factors in Indian non-listed real estate funds

Abstract: Purpose Investment in non-listed real estate funds (NREFs) in an emerging economy like India has its own challenges that entail a detailed understanding of the risks. The purpose of this paper is to identify the key risk factors across the life cycle of a NREF, based on a considered feedback of various real estate fund management stakeholders. It is important for the investors and fund managers to appreciate these risk factors to make informed investment decisions. Design/methodology/approach The present stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 10 publications
(19 citation statements)
references
References 47 publications
0
19
0
Order By: Relevance
“…They found money supply, real GDP growth, interest rate, stock market return and components of inflation impact funds' returns, along with investment style, vintage, size, gearing and vehicle structure. In emerging economies, there are even fewer studies on NREF risk factors; this includes Gupta et al (2018), who identified NREFs' risk factors in India. The present study has used their findings to develop a robust risk assessment framework for real estate portfolio management for NREFs in India.…”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…They found money supply, real GDP growth, interest rate, stock market return and components of inflation impact funds' returns, along with investment style, vintage, size, gearing and vehicle structure. In emerging economies, there are even fewer studies on NREF risk factors; this includes Gupta et al (2018), who identified NREFs' risk factors in India. The present study has used their findings to develop a robust risk assessment framework for real estate portfolio management for NREFs in India.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Gupta et al (2018) have identified 39 risk attributes, which were summarized into five factors using factor analysis and partitioned into risk bands using Euclidean distance. They categorized these five factors into three levels of risk as macro (market risk), meso (enterprise risk) and micro (property risk) risk as shown in Figure 1; Keeris (2008) has classified these risks as systematic, specific and management risk.…”
Section: Generic Nref Risk Framework and Ahp Decision Treementioning
confidence: 99%
See 3 more Smart Citations